Reakcja organizacji na zmiany innowacyjne w kontekście zagrożenia kryzysem - Wawrzynek, Łukasz (Organizational Reaction of the Innovational Changes in the Context of Crisis Threat, 2006)
This paper concerns problem of innovation changes in there relations with crisis phenomena in the organization. The chances as well as the risk connected with this kind of changes are pointed out. The conditions for effective introduction of changes were given, with guarantee the positive results for the organization.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 183-188